Initial brain CT scan and shunting outcomes in children with hydrocephalus - Andi Anita Utami; Alifiani Hikmah Putranti; Yetty Movieta Nency; Eddy Sudijanto (Paediatrica Indonesiana, 2013)
Background Hydrocephalus is one of the most common clinicalconditions affecting the central nervous system, with a congenitalhydrocephalus incidence of 3-4 per 1000 births. Incidence ofacquired types of hydrocephalus is unknown. Brain computerisedtomography (CT) scan can be used to assess the size of ventriclesand other structures. Shunting has long been performed toalleviate hydrocephalus. Shunting has dramatically changed theoutlook of children with hydrocephalus, with many of them havingnormal life expectancies and attaining normal intelligence.Objective To determine the outcomes of shunting in childrenwith hydrocephalus based on initial brain CT scan.Methods We performed a cross-sectional study in Dr. KariadiHospital. Initial brain CT scan data were collected from themedical records of children admitted to the Neurosurgery Wardfor ventriculoperitoneal (VP) shunt surgery from January 2009to December 2010. We studied the brain CT scan findings beforeVP shunt surgery and the outcomes of the children after VP shuntsurgery. Radiological findings were determined by a radiologistresponsible at that time.Results This study consisted of 30 subjects, 19 boys and 11girls. Initial brain CT scans to assess disease severity revealed thefo llowing conditions: lateral ventricle dilatation in 7 subjects,lateral and third ventricle dilatation in 16 subjects, and lateral,third and fourth ventricle dilatation in 7 subjects. After VPshunt surgery, 3 subjects in the lateral, third and fourth ventricledilatation category died. They were grouped according to theircondition. Group 1 consisted of subjects with only lateral ventricledilatation and subjects with lateral and third ventricle dilatation(23 subjects), while group 2 consisted of subjects with lateral,third and fourth ventricle dilatation (7 subjects). More survivorswere found in group 1 than those in group 2.Conclusion Less severe initial brain CT scan findings areassociated with better shunting outcomes children withhydrocephalus.